2011
DOI: 10.1007/s00430-011-0216-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-2 and interleukin-6 mediate cardiomyocyte protection from apoptosis during Trypanosoma cruzi murine infection

Abstract: Local innate immunity plays a key role in initiating and coordinating homeostatic and defense responses in the heart. We have previously reported that the cardiotropic parasite Trypanosoma cruzi, the etiological agent of Chagas disease, protects cardiomyocytes against growth factor deprivation-induced apoptosis. In this study, we investigated cardiomyocyte innate immune response to T. cruzi infection and its role in cellular protection from apoptosis. We found that Toll-like receptor (TLR) 2-expressing cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Moreover, IL-6 diminished the nitration rate and improved the survival of CD8+ T cells. In agreement with this result, we have previously shown that IL-6 acts as a survival factor for infected target cells (28, 29). We have observed that IL-6 regulates IL-1β-induced NO production, and that excessive oxidative stress accounts for the increased mortality of T. cruzi -infected IL6KO mice (unpublished results).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, IL-6 diminished the nitration rate and improved the survival of CD8+ T cells. In agreement with this result, we have previously shown that IL-6 acts as a survival factor for infected target cells (28, 29). We have observed that IL-6 regulates IL-1β-induced NO production, and that excessive oxidative stress accounts for the increased mortality of T. cruzi -infected IL6KO mice (unpublished results).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the increased levels of IL-6 detected in APCP-treated hearts, it is important to stress that this pleiotropic cytokine is a cardioprotective factor. In this sense, we have reported that IL-6 is secreted by cardiomyocytes after T. cruzi recognition, and it acts as a key survival factor for these target cells during the infection (43)(44)(45).…”
Section: Discussionmentioning
confidence: 98%
“…Deletion of IL‐6 was consistently shown to be beneficial against fibrotic heart disease 29. However, IL‐6 seems to exert pleiotropic effects and control the balance between anti‐ and proapoptotic pathways 30, 31. The exact role of IL‐6 signaling in atrial cardiomyocyte apoptosis induced by RA needs to be further investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%